The Effects of Sexual and Gender Based Violence on Psycho-Socio Development of In-School Adolescent Girls in Alimosho Local Government Area of Lagos, Nigeria - Daodu, Morufu Adedayo; Elegbede, Christie Bola (Journal of Advanced Psychology, 2023)
Purpose: The study focused on the effect of sexual and gender-based violence on the psycho-socio development of in-school adolescents in Alimosho Local Government Area of Lagos State, Nigeria. One hundred randomly selected in-school Adolescents girls constitute the sample of the study. Methodology: The study adopted descriptive survey method as a research design. Chi-square statistical method was used to analyze the data gathered from the respondents. Findings: The findings of the study indicated that sexual and gender based violence have significant effects on the psychosocial development of in-school adolescent girls. Unique Contribution to Theory, Policy and Practice: Among others, it was recommended that all hands must be on deck to protect adolescent girls from being victims of these psychological threat and evil trend in our societies. The findings of this study will assist policy makers both in Educational sector and society at large to come up with policies that will protect Adolescent male and female from being a victim of sexual and gender base violence